How to Build a Modern Romanian Nation-State? Authoritarianism versus Parliamentarianism at Mid-19th Century - Manuel Gutan (GLOSSAE. European Journal of Legal History, 2018)
This paper aims to emphasize the existence, between 1859 and 1866, of a sincere fight of the Romanian political elite for the liberal constitutionalism, generally, and for the parliamentary regime, especially, that constantly aimed to eliminate or, at least, to limit the authoritarian rule of the Prince. I would like to remark the decisive contribution of Cuza’s reign to the birth of the Romanian unitary and modern nation-state without turning the constitutional and political modernization into a minor issue. It is useful to notice and it is important to acknowledge the failure of the liberal constitutionalism during the reign of Cuza but, in the same time, it is important to notice that it was never abandoned, at least as ideology, by a great majority of the Romanian political elite. The liberal constitutionalism did not die with the failure of the parliamentary regime. The years following the fall of Cuza witnessed a strong ideological enthusiasm towards the principles and values of the liberal constitutionalism (although in its ethnocentric understanding). In the same time, the making of the 1866 Constitution proved a full aversion towards Caesarism and a sincere commitment with parliamentarianism as a precondition for a successful modernization of the Romanian state and society.